AI Literacy as an Enabling Capability for Higher-Order Thinking: A Structural Model of Multidimensional Student Engagement - Indra Maulana; Khojanatun Khojanatun; Alifiatun Asyifah (Jurnal Indonesia Sosial Teknologi, 2026)
The integration of artificial intelligence (AI) in higher education is transforming learning processes and requires students to develop adequate AI literacy to effectively engage with AI-mediated learning environments. However, limited research has examined how AI literacy contributes to the development of higher-order thinking skills through student engagement mechanisms. This study aims to investigate the role of AI literacy in enhancing critical thinking and logical reasoning, with multidimensional student engagement behavioral, cognitive, and social engagement as mediating variables. A quantitative research design was employed using a structural equation modeling (SEM) approach to analyze the relationships among the proposed constructs. The findings reveal that AI literacy significantly influences students’ behavioral, cognitive, and social engagement in learning activities. Furthermore, the three dimensions of engagement significantly contribute to the development of higher-order thinking skills, with cognitive engagement showing the strongest effect. The results also indicate that AI literacy has a direct and significant impact on both critical thinking and logical reasoning. These findings suggest that AI literacy functions as an enabling capability that supports deeper learning processes through increased student engagement. This study contributes to the literature by providing empirical evidence of the mechanism through which AI literacy promotes higher-order thinking in AI-supported educational environments and highlights the importance of integrating AI literacy development into higher education curricula.